Analysis of Debt Market Innovation, Capital Formation, and Real Economic Growth in Nigeria - Patrick Omoyuri Eke; Omowunmi Awawu King; Oluseyi Olukoya Odufuwa (Jurnal Inspektorat, 2026)
This study tests the market innovation theory, and the finance-leading and growth-following hypotheses. It examined the impact of matrix of debt market, that is, private domestic debt (PDBT), private external debt (PXDBT), and sovereign debt (SBND) on gross-fixed capital formation (GFCF) and real-gross domestic growth rate (RGDPGR) in Nigeria. Institutional quality (IQT) and interest rate (INRT) are control variables. Two-stage least square (TSLS) and Granger-causality techniques were utilized. Data were obtained from Central Bank of Nigeria (CBN) statistical bulletin and the World Bank (WB) database from 1980 to 2023. The study found that PDBT, PXDBT, and SBND drives GFCF, while GFCF drives RGDPGR respectively. However, SBND’s impact on GFCF is relatively very weak, while the impact of SBND on Rdgpgr is negative, as private issued debts outperformed sovereign debt. Both results suggest superiority of private debt yield over SBND yield, and hence, affirms Thomas Piketty’s hypothesis of higher returns on private wealth (r) over return on output (g). Bi-directional causalities operate between IQT and GFCF, and IQT and PDBT respectively. The study thus upholds the market innovation theory, the finance-leading hypothesis, and the credit-quality-spread theory. The study suggests institutional and regulatory reforms, among others.